Pengaruh Proses Stress Relieving Terhadap Nilai Kekerasan Nilai Kekerasan Pipa Setelah Proses Swaging - Rivaldo Rimo; Nurul Laili Arifin; Tian Havwini (Jurnal Teknologi dan Riset Terapan (JATRA), 2022)
Stress relieving is a heat treatment process that aims to eliminate stress on the end of the material that has been deformed, either internal deformation (swaging) or external deformation (expanding). This treatment aims to eliminate residual stress or residual hardness resulting from the end-sizing process and restore the stress level in the pipe due to the swaging process by heating the material according to the temperature and formation of the material itself. While swaging is a forging process on the pipe cylinder to reduce the end of the pipe, as well as forming the end of the pipe according to the request of the customer, both internal and external deformation processes. This study aims to compare the hardness value of pipe material in non-swaging, swaging, and swaging + stress relieving treatments. This test uses carbon steel material grade L80 pipe size 3 ½ inches with a pipe length of 6 ft. The pressure applied during swaging was 2,850 psi for 30 seconds, with a swage stroke value of 118.00 mm. While the stress-relieving treatment is given heating in the temperature range of 595oC – 625oC with a soaking time of 60 seconds. Of the three treatments, the highest hardness was obtained from the swaging process with a value of 19.2 HRC while the lowest hardness was shown by the non-swaging specimen with a value of 16.7 HRC.